Zircon melt inclusions in mafic and felsic rocks of the Bushveld Complex: constraints for zircon crystallization temperatures and partition coefficients - Gudelius, Dominik; Zeh, A.; Almeev, R. R.; Wilson, A. H.; Fischer, L. A.; Schmitt, Axel Karl (Geochimica et cosmochimica acta, 2020)
Melt inclusions in zircon represent time capsules, which provide deep insights into igneous rock formation including timing, physicochemical conditions, and the compositional evolution of cogenetic magmas with respect to major, trace, and volatile elements. However, their full potential as petrogenetic indicators, in particular their usability and consistency as geothermometers, is poorly investigated. Therefore, we present new mineralogical and chemical data for recrystallized and homogenized melt inclusions and host zircon from different mafic and felsic rocks of the Bushveld Complex (BC), South Africa. Samples include rutile-bearing cumulate rocks of the Marginal and Critical zones, as well as rutile-free, magnetite-ilmenite-titanite-bearing diorites and granites of the Upper Zone, Rashoop Granophyre and Lebowa Granite Suite. All melt inclusions, irrespective of rock type, have rhyolitic compositions with SiO2 contents ranging from 65 to 78wt.%, and H2O from 1.6 to 4.0wt.%, whereas trace element contents differ systematically between rock types. In rutile-bearing mafic rocks, melt inclusions commonly show higher Ti contents (>800ppm), higher Th/U ratios (up to 38), and lower REE contents (ƩREE<150ppm) compared to those in rutile-free mafic and felsic rocks (Ti<800ppm; Th/U<5; ƩREE>150ppm). Liquidus temperatures of melt inclusions obtained from normative Qz-Ab-Or and rhyolite-MELTS modelling indicate melt entrapment mostly at 930-850°C (at 200MPa), tailing down in some samples to 700°C. For rutile-bearing rocks, these temperatures overlap with those obtained by TiO2-in-melt and Ti-in-zircon geothermometry. For all rutile-free mafic and felsic rocks, reduced TiO2 activities of aTiO2∼0.3 are required for Ti-in-zircon geothermometry, and TiO2rutile∼30wt.% for TiO2 saturation geothermometry, to match temperatures from other geothermometers. Furthermore, partition coefficients obtained from melt inclusion - host zircon pairs are within error identical for mafic and felsic rocks and also reveal no systematic dependency on melt inclusion size, composition and entrapment temperature. The results of this study demonstrate that melt inclusions in zircon are a powerful tool for geothermometry and to constrain magma compositions, H2O contents, and TiO2 activities, which are critical for the understanding of magmatic processes shaping Earth’s crust.